2017
DOI: 10.15171/ijhpm.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Benefits of Healthcare: DALYs and QALYs – Does the Choice of Measure Matter? A Case Study of Two Preventive Interventions

Abstract: Background: The measurement of health benefits is a key issue in health economic evaluations. There is very scarce empirical literature exploring the differences of using quality-adjusted life years (QALYs) or disability-adjusted life years (DALYs) as benefit metrics and their potential impact in decision-making. Methods: Two previously published models delivering outputs in QALYs, were adapted to estimate DALYs: a Markov model for human papilloma virus (HPV) vaccination, and a pneumococcal vaccination determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
0
32
0
4
Order By: Relevance
“…Incremental cost‐effectiveness ratios (ICER) between the PEP and non‐PEP groups were calculated by dividing the difference in cost by the difference in QALYs. The ICERs were compared with the willingness to pay (WTP) threshold for a QALY according to the WHO guideline that interventions with a cost per QALY gained of less than 1 × GDP per capita (HK $359 996 or US $ 46 153 in 2017) would be considered highly cost‐effective …”
Section: Methodsmentioning
confidence: 99%
“…Incremental cost‐effectiveness ratios (ICER) between the PEP and non‐PEP groups were calculated by dividing the difference in cost by the difference in QALYs. The ICERs were compared with the willingness to pay (WTP) threshold for a QALY according to the WHO guideline that interventions with a cost per QALY gained of less than 1 × GDP per capita (HK $359 996 or US $ 46 153 in 2017) would be considered highly cost‐effective …”
Section: Methodsmentioning
confidence: 99%
“…Second, the medical costs after the basic medical insurance is insured [28,29]. Most scholars have observed that participation in basic medical insurance does not significantly reduce the actual medical expenditure of the insured [30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, comparing them requires the assumption that the quality of life associated with a health condition is equivalent to the level of disability it confers. 37 Health opportunity costs are relevant regardless of how the HCS is financed; they exist in systems that are primarily government funded as well as those that are primarily privately funded. When a new treatment displaces a treatment currently available in a government-funded HCS, health opportunity costs may manifest in a number of ways, such as the extension of waiting times for existing procedures.…”
Section: Discussionmentioning
confidence: 99%